2016
DOI: 10.1038/srep20587
|View full text |Cite
|
Sign up to set email alerts
|

TGFβ3-mediated induction of Periostin facilitates head and neck cancer growth and is associated with metastasis

Abstract: The matrix-specific protein periostin (POSTN) is up-regulated in human cancers and associated with cancer growth, metastasis and angiogenesis. Although the stroma of cancer tissues is the main source of POSTN, it is still unclear how POSTN plays a role to facilitate the interplay between cancer cells and cancer-associated fibroblasts (CAFs) in head and neck cancer (HNC), thereby promoting tumorigenesis via modifying the tumor microenvironment. Herein, we have performed studies to investigate POSTN and its role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
84
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 58 publications
(77 reference statements)
6
84
0
1
Order By: Relevance
“…POSTN plays a functional role in the regeneration of tissues such as bone and heart, promotes wound healing and is frequently up‐regulated in various types of human cancers and is implicated in cancer cell proliferation, invasion, and metastasis . However, whether POSTN is associated with the effect of BMMSC on HNC had not yet been previously addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POSTN plays a functional role in the regeneration of tissues such as bone and heart, promotes wound healing and is frequently up‐regulated in various types of human cancers and is implicated in cancer cell proliferation, invasion, and metastasis . However, whether POSTN is associated with the effect of BMMSC on HNC had not yet been previously addressed.…”
Section: Discussionmentioning
confidence: 99%
“…POSTN plays a functional role in the regeneration of tissues such as bone and heart, promotes wound healing and is frequently upregulated in various types of human cancers and is implicated in cancer cell proliferation, invasion, and metastasis. 31,32 However, whether POSTN is associated with the effect of BMMSC on HNC had not yet been previously addressed. In this study, we found that MSC-CM could promote the expression of POSTN possibly because BMMSC could secrete many kinds of cytokines into MSC-CM such as interleukin-6 (IL-6), interleukin-10 (IL-10), vascular endothelial growth factor (VEGF), transforming growth factor beta (TGF-b) etc.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, periostin has also been localized in infarcted myocardium Oka et al 2007), fibrosis (Okamoto et al 2011;Ishikawa et al 2014;Naik et al 2012;Takayama et al 2006;Uchida et al 2012), tissues undergoing wound healing (Nishiyama et al 2011;Norris et al 2007;Ontsuka et al 2012;Zhou et al 2010), and cancer-associated stroma (Fukushima et al 2008;Kashima et al 2009;Kikuchi et al 2008Kikuchi et al , 2014Liu et al 2014;Nitsche et al 2016;Oskarsson and Massague 2012;Qin et al 2016;Ruan et al 2009;Sung et al 2016;Tian et al 2015;Underwood et al 2015;Wang and Ouyang 2012). Taken together, periostin expression is well correlated with tissue regeneration (Conway et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…For instance, periostin promotes the secretion of fibronectin from fibroblasts and participates in extracellular matrix remodeling [18]. It has been reported that periostin modulates head and neck cancer growth and metastasis [19]. In tumor microenvironment, periostin shows the ability to regulate many aspects of endothelial cells, facilitating tumor angiogenesis [20].…”
Section: Introductionmentioning
confidence: 99%